2022
DOI: 10.1021/acsami.2c11677
|View full text |Cite
|
Sign up to set email alerts
|

Balancing Lattice Strain by Embedded Ionic Liquid for the Stabilization of Formamidinium-Based Perovskite Solar Cells

Abstract: Formamidinium (FA)-based perovskites remained state-of-the-art in the field of perovskite solar cells (PSCs) owing to the exceptional absorption and carrier transport properties, while the transition from photoactive (α-) to photoinactive (δ-FAPbI 3 ) phase is the impediment that causes performance degradation and thus limits the deployment of FA-based PSCs. The unfavorable phase transition originates from tensile strain in the FAPbI 3 crystal lattice, which undergoes structural reorganization for lattice stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…This leads to a change in the electronic band‐edge structure, particularly in the valence band edge, and has the ability to modulate the E g . [ 8b ] The location of the conduction band minimum of Cs–FA is similar to that of pure FAPbI 3 . [ 44 ] Considering the valence band maximum (VBM), the declined average Pb─I─Pb angles lead to a stronger PbI 6 octahedral tilting, [ 45 ] leading to the descending location of VBM, wherein the enlarged bandgap is macroscopically exhibited.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…This leads to a change in the electronic band‐edge structure, particularly in the valence band edge, and has the ability to modulate the E g . [ 8b ] The location of the conduction band minimum of Cs–FA is similar to that of pure FAPbI 3 . [ 44 ] Considering the valence band maximum (VBM), the declined average Pb─I─Pb angles lead to a stronger PbI 6 octahedral tilting, [ 45 ] leading to the descending location of VBM, wherein the enlarged bandgap is macroscopically exhibited.…”
Section: Resultsmentioning
confidence: 93%
“…Owing to the large size of FA + ions, the crystal lattice is inclined to release lattice strain and distort to the yellow phase at room temperature. [ 8 ] After the introduction of CsCl, the phase stability is substantially strengthened owing to the optimized tolerance factor; however, the ionic radius mismatch with FA + results in compressive strain owing to the weak Pb─I─Pb bond owing to (PbI 6 ) − tilting, [ 3b,30 ] which leads to lattice contraction and an enlarged E g . In the case of CsCl:Eu 3+ , the presence of Eu 3+ in the interstitial site moderates the Cs‐induced local strain and offsets the Cs + ‐induced lattice contraction.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that the energy levels of the perovskite layers, charge transporting layers and electrodes are mainly Fig. 19 Chemical structures of BMPBr, 135 EMIFAP, 136 choline bromide, 137 HDZWs, 138 DTPT 140 and APSA. 144 determined by the nature of the materials, a well-matched energy level alignment can be achieved by the utilization of suitable materials.…”
Section: Energy Level Alignmentmentioning
confidence: 99%
“…134 Duan et al introduced an IL additive, BMPBr, into the FAPbI 3 lattice and fabricated PSCs with significantly enhanced stability through a strain balancing strategy. 135 The electrostatic interactions between BMP + and the uncovered iodide anions at the grain boundaries induced compressive strains in the crystal lattice. DFT calculation indicated that the embedded IL led to a decrease in the Pb–I–Pb average bond angle, and thus the Pb–Pb average distance along the out-of-plane direction was reduced from 6.61 to 6.40 Å.…”
Section: Improvement Of Crystalline Propertymentioning
confidence: 99%